Revision of the Amphilius jacksonii complex (Siluriformes: Amphiliidae), with the descriptions of five new species - Thomson, Alfred W.; Page, Lawrence M.; Hilber, Samantha A. (Zootaxa, 2015)
The Amphilius jacksonii complex is revised, and five new species are described: A. ruziziensis n. sp. from the Ruzizi River drainage and northeastern tributaries of Lake Tanganyika; A. pedunculus n. sp. from the Malagarasi River drainage, Lake Rukwa basin, and upper Great Ruaha River drainage, Rufiji basin; A. frieli n. sp. from the upper Congo basin; A. crassus n. sp. from the Rufiji and Wami basins; and A. lujani n. sp. from the Lake Kyogo drainage, northeastern tributaries of Lake Victoria, and the Lake Manyara basin.